2009
DOI: 10.1021/cg900381h
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Formation of Titanate Nanotubes and the Transformation Mechanism of Nanotubes into Nanowires

Abstract: Large-scale pure titanate nanotubes were synthesized through the hydrothermal reaction between TiO 2 powders and concentrated NaOH under an unexpected high temperature of 240 °C, while it was generally claimed that it is impossible to form nanotubes at temperatures higher than 180 °C. The titanate nanotube was found to be an inevitable intermediate product, which finally transformed into a nanowire upon increasing the hydrothermal treatment duration. It was proven that the successive appearance of nanosheets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 32 publications
7
52
1
6
Order By: Relevance
“…These also show the presence of unreacted TiO2 nanoparticles. For CH 130-48, we noted the presence of non-tubular or nanoribbon structures (Figure 4b) as reported in other studies (Bavykin et al, 2004;Huang et al, 2009). This explains the low surface area and pore volume presented for this sample.…”
Section: -supporting
confidence: 85%
See 1 more Smart Citation
“…These also show the presence of unreacted TiO2 nanoparticles. For CH 130-48, we noted the presence of non-tubular or nanoribbon structures (Figure 4b) as reported in other studies (Bavykin et al, 2004;Huang et al, 2009). This explains the low surface area and pore volume presented for this sample.…”
Section: -supporting
confidence: 85%
“…This explains the low surface area and pore volume presented for this sample. According to Huang et al (2009), higher reaction times favor the formation of nanoribbons. This is due to dissolution of the nanotube by precipitation of Ti (IV) in the inner and outer surface of the nanotubes, which fills the tube and pores.…”
Section: -mentioning
confidence: 99%
“…Of particular interest, the hydrothermal treatment method has received great attention owing to the fairly simple synthesis, low cost processing, chemical versatility, and scalability [19][20][21][22][23]. Anil et al [9] have shown that Cu-doping increases the catalytic activity of Mn3O4 for CO oxidation.…”
Section: Morphology and Elements Distributionmentioning
confidence: 99%
“…• (indicated by stars), which can be attributed to trititanate [9,11], are also be observed in the XRD pattern of the nanowire film.…”
Section: Resultsmentioning
confidence: 80%
“…As one of the most effective methods for preparation of 1D titanate nanostructures, the method of hydrothermal treatment of TiO 2 in concentrated alkali solutions has gained great attention [8][9][10][11][12][13] since the pioneering work of Kasuga et al [14]. In general, under relatively lower temperature (e.g.…”
Section: Introductionmentioning
confidence: 99%